Structural interpretation of the Steenkampskraal monazite deposit, Western Cape, South Africa. (September 2016) - Basson, I.J.; Muntingh, J.A.; Jellicoe, B.C.; Anthonissen, C.J.
Abstract: The Steenkampskraal Monazite Mine was first established in 1952, to extract monazite ore for the production of thorium and rare earth element (REE) concentrate. Refurbishment of the mine in recent years has required the re-inspection and re-evaluation of the mineralized monazite zone (MMZ). This contribution presents a structural review of the MMZ and its emplacement, based on recent data and its setting at the southern extent of the Bushmanland Sub-province of the Namaqua-Natal Metamorphic Belt. New surface and underground mapping confirm that the MMZ is a moderately-dipping body within gneissic host rocks on the southern limb of a broad F3 antiform. Thickness variations, both down-dip and along-strike, are the result of D2 and D3 deformation. The MMZ has been locally transected and steepened by subsequent late-D3, "steep-structures", which are typical of the Okiep copper district, ∼150 km north of Steenkampskraal. Geochronological data suggest that the MMZ was intruded, emplaced or formed at 1046 ± 7.5 Ma, at the start of the D3 Klondikean Episode (1040–1020 Ma). Unlike the analogous copper-bearing Koperberg Suite in the Okiep Copper district, the MMZ was not intruded into Klondikean-aged steep structures, but was rather transected and steepened by these. Local steepening of the otherwise moderately-dipping to flat-lying MMZ makes it locally amenable to detection by soil sampling and radiometric surveys. Highlights: The Mineralized Monazite Zone (MMZ) at Steenkampskraal mine is a monazite-dominated body in a broad F3 antiform. The MMZ shows variable thicknesses across the mine and has a chocolate-tablet geometry. Geochronological data suggest that the MMZ was formed at 1046 ± 7.5 Ma, at the start of the D3 "Klondikean" episode. The MMZ was not intruded into "steep structures"of the Bushmanland Sub-province, but is transected and steepened by these.